Karakterisasi sifat fisik dan kimia tepung kecambah sorgum merah (Sorghum bicolor) pada berbagai waktu perkecambahan - Ni Wayan Wisaniyasa; Nengah Kencana Putra; Moreen Alesandrina Nicole (AGROINTEK, 2025)
Red sorghum is a cereal plant that can be utilized as a carbohydrates source with high content of protein and antioxidants activity, but it has anti- nutritional compounds such as tannins. The germination process can improve the physical and chemical properties of materials including protein digestibility and antioxidant activity. This research aims to determine the effects of germination time on physical and chemical properties of red sorghum sprouts flour and determine the ideal germination time to produce red sorghum sprout flour with the highest protein digestibility and antioxidant activity. This study used a Completely Randomized Design with five treatment levels of germination time: 0, 12, 24, 36, and 48 hours, each repeated three times. Parameters observed in this study included water content, protein content, tannin content, protein digestibility, antioxidant activity, and color analysis (L*, a*, b*). The data obtained were analyzed using variance analysis. The results of the research show that the germination time significantly affects protein digestibility, antioxidant activity, protein content, tannin content, and the color parameters lightness, redness, and yellowness of malted red sorghum flour, but does not affects its water content. The ideal germination time of red sorghum based on this research is 48 hours, which produce malted red sorghum flour that contains water content 7.67%, protein content 9,08%, tannin content 0.38%, protein digestibility 79.49%, antioxidant activity (IC50) 147.44 ppm, and color analysis (lightness 74.03, redness 1.60, yellowness 10.67)(yellowish white with a slight red hue).